Healthy Aging – Insights from Drosophila - Iliadi, Konstantin G.; Knight, David; Boulianne, Gabrielle L. (Frontiers in Physiology, 2012)
Human life expectancy has nearly doubled in the past century due, in part, to social and economic development, and a wide range of new medical technologies and treatments. As the number of elderly increase it becomes of vital importance to understand what factors contribute to healthy aging. Human longevity is a complex process that is affected by both environmental and genetic factors and interactions between them. Unfortunately, it is currently difficult to identify the role of genetic components in human longevity. In contrast, model organisms such as C. elegans, Drosophila and rodents have facilitated the search for specific genes that affect lifespan. Experimental evidence obtained from studies in model organisms suggests that mutations in a single gene may increase longevity and delay the onset of age-related symptoms including motor impairments, sexual and reproductive and immune dysfunction, cardiovascular disease and cognitive decline. Furthermore, the high degree of conservation between diverse species in the genes and pathways that regulate longevity suggests that work in model organisms can both expand our theoretical knowledge of aging and perhaps provide new therapeutic targets for the treatment of age-related disorders.